Improving Problem-Solving Skills Using ESD Integrated PBL Models Assisted with the Greenhouse Limas Project - Qiroah, Innita Fashihatul; Lestari, Nurita Apridiana (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2024)
Improving Problem-Solving Skills Using ESD Integrated PBL Models Assisted with the Greenhouse Limas Project. Problem-solving skills in high school students are still low, there are still many students who have not been able to develop problem-solving so innovative learning models are needed in learning at school. This study aims to describe the implementation of the ESD-integrated PBL model utilizing greenhouse lime to improve students' problem-solving skills. The type of research used in the research is this research using the type of Quasi-Experimental Design research. The participants in this study are students of class X Mipa at one of the high schools in Pamekasan Regency. This study uses 2 classes, namely the control class and the experimental class. Based on the results of the research, it was concluded that the ESD-integrated PBL model learning activities to improve the solving skills of class X students were carried out with an average percentage of 95.55% in the very good category. The application of ESD-integrated PBL model learning can improve students' problem-solving skills. This is characterized by 1) the results obtained from the post-test score are higher than the results of the pre-test with an N-Gain of 0.78 in the high category, while in the control class, the results of the N-Gain obtained are 0.67 with the medium category 2) the results of the post-test of the two classes in the independent test are 0.162 which means that the significant value is greater than 0.05, then H1 is accepted. Thus, there was a significant difference in the mean post-test scores of the experimental class and the post-test of the control class. Students' responses to the application of ESD-integrated PBL model learning to improve students' problem-solving skills based on the analysis of the response questionnaire obtained a positive response in the experimental class with an average percentage above 70%, which means that the points on the student response questionnaire were in a good category.